Relationship between Organisational E-readiness and E-Commerce Implementation in Developing Countries: Perspectives from Tanzania - Mbamba, Ulingeta O.L. (University of Dar es Salaam Library Journal, 2023)
This paper aimed to establish the role of e-readiness in implementing e-commerce in organisations in developing countries using Tanzania as an example. Using Molla and Licker ' s (2005a) model, the study evaluated the organisational e-readiness to implement e-commerce. Data collected via email came from 165 purposively selected managers from Dar es Salaam. The resultant data were subjected to confirmatory factor analysis to reduce the number of variables to a manageable level. Then the e-readiness factors were regressed to the level of e-commerce. The results show that organisational commitment, technological resources, and awareness level, as well as the government ' s commitment to e-readiness emerged to be important factors in determining the level of e-commerce of an organisation. Empirically, the study shows that these four factors are reliable predictors of the e-commerce level from the developing countries ' perspectives. All the variables identified were significantly related to the level of e-commerce an organisation has attains. Thus, the paper argues that an organisation ' s commitment, technological resources and awareness level, as well as the government ' s commitment to e-Readiness are salient factors in determining the e-commerce level of implementation of an organisation. Implicitly, the factors the paper has identified are important in the execution of e-commerce. As such, these factors need consideration in an organisation seeking to benefit from e-commerce implementation. In other words, countries can ignore e-readiness and e-commerce implementation at their own peril.